Kompetensi dan Profesionalisme terhadap Kualitas Audit melalui Etika Auditor sebagai Variabel Mediasi di Lingkungan Aparat Pengawas Intern Pemerintah (APIP) Kabupaten Boven Digoel - Muhammad Sahrul (IPM2KPE, 2024)
This research aims to investigate the impact of competence and professionalism on audit quality by integrating auditor ethics as a mediating variable. The research method applied is a quantitative method, using Partial Least Square (PLS) analysis to analyze the collected data. The research results show that competence and professionalism have a positive and significant influence on audit quality, both directly and through the role of auditor ethics as a mediating variable. Conclusion, understanding of the factors that influence audit quality in the accounting profession. The practical implication of this research is that increasing auditor competence and professionalism can improve audit quality, with auditor ethics acting as an intermediary in this relationship. Keywords: Government Internal Supervisory Apparatus (APIP), Auditor Ethics, Auditor Competence, Audit Quality, Auditor Professionalism